2016
DOI: 10.1016/j.ymgmr.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between age and white matter integrity in children with phenylketonuria

Abstract: Diffusion tensor imaging (DTI) has shown poorer microstructural white matter integrity in children with phenylketonuria (PKU), specifically decreases in mean diffusivity (MD), in comparison with healthy children. However, little research has been conducted to investigate the relationship between age and white matter integrity in this population. The present study examined group differences in the relationship between age and MD across a range of brain regions in 31 children with early- and continuously-treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Finally, decreased MD values have been previously shown to correlate with increased age [ 8 , 11 , 12 ] in PKU children, which further supports the results shown in this work. MD and RD are thought to be a good marker of myelin structure and, in healthy populations, decreased RD and MD values are usually associated to a better WM microstructure [ 2 , 40 , 60 , 61 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Finally, decreased MD values have been previously shown to correlate with increased age [ 8 , 11 , 12 ] in PKU children, which further supports the results shown in this work. MD and RD are thought to be a good marker of myelin structure and, in healthy populations, decreased RD and MD values are usually associated to a better WM microstructure [ 2 , 40 , 60 , 61 ].…”
Section: Discussionsupporting
confidence: 91%
“…White et al [ 8 ] showed MD restriction values in the anterior part of the CC (genu and rostral body). Wesonga et al [ 12 ] demonstrated significant abnormal diffusion values in the genu and splenium of the CC. In contrast, we found decreased of MD values but also RD decreased values in the body and splenium of the CC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The white matter pathology observed in PKU patients is diffuse throughout the brain and worsens with age, and it seems to participate in the decline of executive functions due to non-adherence to the treatment (Hawks et al, 2019). To illustrate, the microstructural development of white matter is progressively impaired in PKU children (Wesonga, Shimony, Rutlin, Grange, & White, 2016), affecting inferior executive abilities in PKU patients at different ages (Antenor-Dorsey et al, 2013).…”
Section: Cn S Demyelinati On In Pkumentioning
confidence: 99%
“…Whether the observed retinal changes relate to WML burden remains speculative as MRI scans were not available in any of the OCT studies (38)(39)(40), including ours. However, WMLs have repeatedly been described in ETPKU patients with the underlying molecular mechanisms remaining elusive (17)(18)(19)(59)(60)(61)(62)(63). Intramyelinic edema is primarily thought to be responsible for reversible WMLs (17), but impairment of microstructural development has also been described (59).…”
Section: Discussionmentioning
confidence: 99%